Analisis dan Rekonstruksi Desain Kegiatan Laboratorium Keanekaragaman Makhluk Hidup : (Analysis and Reconstruction of The Design of Living Creature Diversity Laboratory Activities) - Juniarti, Mia Angriana; Supriatno , Bambang; Amprasto, Amprasto (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
Lab activities can guide students in constructing knowledge through a process of operational steps. However, most laboratory activities in the field are not appropriate with the content taught so that students cannot construct factual knowledge into conceptual knowledge, especially in studying the diversity of creatures. The aim of this study is to provide an overview of the quality of existing practicum activities for the diversity of living things to be tested and reconstructed into a design of laboratory activities to support a better learning process. The research method used is qualitative descriptive method. The flow of research carried out is based on ANCOR (Analysis, Trial, and Reconstruction). The type of sampling technique used is nonprobability sampling with purposive sampling technique. The research sample, practicum activities for the diversity of living things integrated in the class X independent curriculum science book. The results of analysis and trials based on the existence of knowledge construction components found that alternative design of laboratory activities is needed based on knowledge construction indicators in the Diagram Vee. Key words: Analysis, Reconstruction, Design of Laboratory Activities, Classification of Living Things. Abstrak. Kegiatan laboratorium dapat membimbing siswa dalam mengonstruksi pengetahuan melalui serangkaian langkah-langkah operasional. Namun, mayoritas kegiatan laboratorium di lapangan tidak sesuai dengan materi yang diajarkan sehingga siswa tidak dapat mengonstruksi pengetahuan faktual menjadi pengetahuan konseptual terutama dalam mempelajari keanekaragaman makhluk. Tujuan dari penelitian ini untuk memberikan gambaran mengenai kualitas kegiatan praktikum keanekaragaman makhluk hidup yang sudah ada untuk kemudian diuji coba dan direkonstruksi kembali menjadi desain kegiatan laboratorium untuk menunjang proses pembelajaran yang lebih baik. Penelitian ini menggunakan metode deskriptif kualitatif dengan pengumpulan data melalui analisis lembar kegiatan praktikum untuk menentukan lembar kegiatan praktikum biologi kelas X yang kurang sesuai dan analisis komponen desain kegiatan praktikum berdasarkan Diagram Vee. Berdasarkan alur tahapan dalam perancangan desain kegiatan laboratorium berbasis ANCOR (Analisis, Uji Coba, dan Rekonstruksi), diperlukan alternatif desain kegiatan laboratorium berdasarkan indikator konstruksi pengetahuan dalam Diagram Vee. Kata kunci: Analisis, Rekonstruksi, Laboratorium, Klasifikasi Makhluk Hidup.